Aksesibilitas Permodalan Perbankan bagi Wirausahawan Difabel di D.I Yogyakarta untuk Mewujudkan Ekonomi Inklusi - Diska Arliena Hafni; Fitri Maulidah Rahmawati (Kompartemen : Jurnal Ilmiah Akuntansi, 2019)
This study aims to determine the opportunities and challenges faced by diffable entrepreneurs in accessing banking capital. In addition, it is also to find out the extent to which the role of banks provides access to capital for diffable entrepreneurs. The study was a descriptive qualitative study involving blind and disabled disabled entrepreneurs who were members of Persatuan Tuna Netra Indonesia (PERTUNI) DIY, Persatuan Penyandang Disabilitas Indonesia (PPDI) DIY area and Ojek Difa DIY motorcycle taxi. Data collection uses interview, observation and documentation methods. Data analysis is done by collecting data, reducing data, presenting data (data display), and drawing conclusions. The results showed that only a small proportion of blind diffable entrepreneurs had interacted with the banking sector, the rest preferred to interact with other financial institutions such as cooperatives established by PERTUNI and BMT. They chose this because banking services were considered to be quite complicated or lacking in access for blind diffable entrepreneurs. On the other hand, disabled entrepreneurs have often interacted with banking and there are no significant problems in the process of lending bank capital. However, both the disabled and forced entrepreneurs hope there will be an increase in services for diffable entrepreneurs primarily in terms of facilities and infrastructure as well as more diffable-friendly banking service products.Keywords: accesisbility of banking capital, diffable entrepreneurs, economic inclusion